Hypoglycemia unawareness among insulin-treated diabetic patients in Madinah, Saudi Arabia: prevalence and risk factors - Surrati, Amal M. Qasem; Alanazi, Alhanouf Ayed; Bukhari, Samyah Sami; Alfadhli, Eman Mohammed (Frontiers in Endocrinology, 2023)
Hypoglycemia unawareness (HU) is associated with significant risks. Screening for impaired awareness of hypoglycemia in patients with diabetes is important to minimize those risks. There are limited data on the prevalence of HU in patients with diabetes in Saudi Arabia (KSA). In the current study, we investigated the frequency of HU and its risk factors among diabetic patients in KSA.A cross-sectional study was conducted at the Diabetes Center and four Primary Health Care Centers. Patients ≥14 years old with type 1 or type 2 diabetes treated with insulin for more than a year were included. HU was assessed by Clarke's and Modified Pedersen-Bjergaard's scores. The risk factors for HU were determined.Of the 413 included patients, 60.3% were females, and 60.8% were on insulin alone. One-third of participants had T1DM, while 68.5% had T2DM, with median ages of 25 and 56 years, diabetes durations of 10 and 15 years, and durations of insulin use of 10 and 5 years, respectively.The prevalence of HU was 25.2% by Clarke's survey. Poor knowledge of patients' latest HbA1c, type of insulin and dose of insulin were risk factors for HU. Poor medical follow up, previous stroke, and ischemic heart disease, were other risk factors for HU. When the modified Pedersen-Bjergaard method was used, the prevalence of HU was 48.9%.Despite the advances in diabetes management, HU continues to be prevalent among diabetic patients on insulin, and poor diabetes knowledge is a major risk factor. Self-management of diabetes education is of utmost importance to reduce hypoglycemia and HU.